Avaliação da função pulmonar em pacientes tratados para tuberculose na cidade de Belém – Pará - NORONHA, Hirley Gabriel Reimão (2020)
Tuberculosis (TB) is a curable, preventable, and chronic infectious disease, transmitted by aerosol and caused by mycobacterium tuberculosis. In 2018, 956 new cases were confirmed in Belém-PA, thus being the fifth capital in Brazil in relation to the incidence coefficient. It is known that this disease can cause pulmonary sequelae leading to the impairment of respiratory capacity with serious repercussions on patients' quality of life. This is an observational, analytical and cross-sectional study that was conducted in 2018 from January to December. This study aims to evaluate changes in pulmonary function by spirometry in patients treated for TB at University Hospital João de Barros Barreto (HUJBB) in Belém-PA. We used data from 52 participants who underwent treatment for pulmonary tuberculosis (TBP). These patients answered a questionnaire containing the sociodemographic characteristics, signs and symptoms, comorbidities, chest x-ray and bacilloscopy. After completion of the treatment, patients underwent spirometry to assess lung function. Most patients had normal lung function. However, in 46.2% of patients, pulmonary function was altered. Among the altered patterns, 19.3% were restrictive, 17.4% obstructive and 9.5% obstructive with FVC reduction. The risk factors for the development of obstructive disorder in patients treated for TB were smoking, alcoholism and low schooling, while for the restrictive disorder, the presence of high bacillary load was the most important. Therefore, a large number of patients treated for tuberculosis present some type of respiratory dysfunction and should be submitted to evaluation of pulmonary function, especially in those with risk factors, in order to identify the need for a multiprofessional pulmonary rehabilitation follow-up, seeking to reduce the impact of respiratory sequelae caused by tuberculosis infection.